2023
DOI: 10.1021/acs.energyfuels.3c01925
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Utilization from Corn Derivatives for High-Energy-Density Flexible Supercapacitors

Kiran Kumar Reddy Reddygunta,
Rachael Beresford,
Lidija Šiller
et al.

Abstract: Porous activated carbons from four types of corn derivatives (husk, fiber, grain, and cob) are compared for the first time regarding their structural, morphological, and electrochemical characteristics for application as electrode materials in flexible supercapacitors. Benefiting from its hierarchical porous structure, appropriate amount of N and O functional groups, large specific surface area (1804 m 2 g –1 ), and high degree of graphitization, the activated carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Since the 0.2 numerical value is a standard value in Design-Expert 10 (File Version 10.0.7.0) software, from this validation, it is found that the model is adequate for the optimization of three operational parameters. Using the same electrolytes with 6 M KOH, similar work was done by other biomass-based AC, such as chestnut AC, 37 purple corncob AC, 38 (husk, fiber, grain, and cob), 39 Metaplexis japonica-based AC. 40 3.4.…”
Section: Model Validationmentioning
confidence: 99%
“…Since the 0.2 numerical value is a standard value in Design-Expert 10 (File Version 10.0.7.0) software, from this validation, it is found that the model is adequate for the optimization of three operational parameters. Using the same electrolytes with 6 M KOH, similar work was done by other biomass-based AC, such as chestnut AC, 37 purple corncob AC, 38 (husk, fiber, grain, and cob), 39 Metaplexis japonica-based AC. 40 3.4.…”
Section: Model Validationmentioning
confidence: 99%
“…Due to their huge SSA, outstanding conductivity, excellent electrochemical and mechanical durability, carbonaceous materials like carbon nanotubes and graphene are the preferred electroactive materials for EDLCs. , However, because they use fossil fuels as their primary precursors, these materials are not the best options, from a sustainability point of view. Hence, activated carbons from natural biomass sources have garnered a lot of attention in recent years, because of their abundant natural availability, low cost, nontoxic nature, and renewability, as opposed to fossil fuels. Furthermore, biomass activated carbon possess unique features, such as tunable surface chemistry, an interconnected porous framework, and abundant functional groups, which contributes to the excellent electrical conductivity and enhanced charge storage ability. Researcher interest is currently being drawn by a variety of biomass materials, including corn stalks, , hazelnut shells, pine cones, , orange peels, , tree bark, , and others. Biomass-activated carbon possesses significantly enhanced SSA and porosity after physical or chemical activation processes, which might make it easier for the charges to move across layers of the porous carbon structure.…”
Section: Introductionmentioning
confidence: 99%